Reviews of recent publications (Studies in 20th & 21st Century Literature, 2000)
Mieke Bal. The Mottled Screen: Reading Proust Visually by Beryl Schlossman Anny Brooksbank Jones and Catherine Davies, eds. Latin American Women's Writing: Feminist Readings in Theory and Crisis by Rosemary Geisdorfer Feal Tomasa Cuevas. Prison of Women: Testimonies of War and Resistance in Spain, 1939-1975 by Yolanda Molina Gavilán David William Foster. Buenos Aires: Perspectives on the City and Cultural Production by Gustavo Geirola Belinda Jack. Francophone Literatures: An Introductory Survey by Claire L. Dehon Marx-Scouras, Danielle. The Cultural Politics of Tel Quel: Literature and the Left in the Wake of Engagement by Diane Fourny Jeffrey Mehlman. Genealogies of the Text: Literature, Psychoanalysis, and Politics in Modern France by Florence Martin Nancy Shawcross. Roland Barthes on Photography. by Philip Hadlock Lewis W. Tusken. Understanding Hermann Hesse: The Man, His Myth, His Metaphors by Theodore Ziolkowski
Keywords: Mieke Bal; The Mottled Screen: Reading Proust Visually; Beryl Schlossman; Anny Brooksbank Jones; Catherine Davies; . Latin American Women& #x27; s Writing: Feminist Readings in Theory and Crisis; Rosemary Geisdorfer Feal; Tomasa Cuevas; Prison of Women: Testimonies of War and Resistance in Spain 1939-1975; Yolanda Molina Gavilán; David William Foster; Buenos Aires: Perspectives on the City and Cultural Production; Gustavo Geirola; Belinda Jack; Francophone Literatures: An Introductory Survey; Claire L. Dehon; Danielle Marx-Scouras; The Cultural Politics of Tel Quel: Literature and the Left in the Wake of Engagement; Diane Fourny; Jeffrey Mehlman; Genealogies of the Text: Literature Psychoanalysis and Politics in Modern France; Florence Martin; Nancy Shawcross; Roland Barthes on Photography; Philip Hadlock; Lewis W. Tusken; Understanding Hermann Hesse: The Man His Myth His Metaphors; Theodore Ziolkowski